Dampak Halal Certification, Dan Destination Brand Terhadap Behavioural Intention : Efek Mediasi Tourist Satisfaction - Haryeni, Haryeni; Yendra, Nofri (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The aim of this research is to find out: the influence of halal certification on halal culinary on tourist satisfaction, the influence of halal certification on halal culinary on behavioral intention, the influence of destination brand on tourist satisfaction, the influence of tourist satisfaction on behavioral intention, the influence of halal certification on halal culinary on behavioral intention which is mediated by tourist satisfaction, the influence of destination brand on behavioral intention which is mediated by tourist satisfaction. The population in this study were tourists who visited halal tourist destination areas in West Sumatra, namely Padang City. A series of exploratory and confirmatory factor analyzes were used to assess the study constructs, unidimensionality, validity, and composite reliability. The number of samples for this research was 150 respondents. The data analysis technique used in testing this research hypothesis was the use of the Partial Least Square (PLS) program. Based on the research results, Halal Certificate has a significant effect on Behavioral Intention. Halal Certificate has no significant effect on Destination Satisfaction, Destination brand has a significant effect on Destination Satisfaction. Destination Satisfaction has a significant effect on Behavioral Intention. Halal certificate does not moderate the influence between halal certificate and behavioral intention. Meanwhile, destination brand influences behavioral intention which is moderated by destination satisfaction.